2022
DOI: 10.1210/clinem/dgac113
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Lipoproteins and Insulin Sensitivity in Youth With Obesity and Abnormal Glucose Tolerance

Abstract: Objective To determine the association between insulin resistance, dyslipidemia, and carotid intimal thickness (cIMT) in adolescents with normal and abnormal glucose tolerance. Methods An observational cohort study in 155 youth: 44 obese insulin sensitive (OIS;fasting insulin≤20µM/mL, BMI≥95%ile), 35 obese insulin resistant (OIR;fasting insulin>20µM/mL, BMI≥95%ile), 34 obese abnormal glucose tolerant (AGT; BMI≥95%ile),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The effects of vitamin D on glucose homeostasis, exerted mainly by its active form 1,25-dihydroxycholecalciferol, include the increase of peripheral and hepatic glucose uptake, the improvement in synthesis and secretion of insulin, the protection of b-cells from cytokine induced apoptosis and attenuation of inflammation (47, 54-56). It has been confirmed that insulin resistance affects obesity-related pro-atherogenic changes in lipid profile (57,58). Insulin resistance impairs the function of insulindependent hormone-sensitive lipase and lipoprotein lipase, which are involved in lipid metabolism, whereas insulin cannot act effectively due to obesity and dyslipidaemia (59,60).…”
Section: Discussionmentioning
confidence: 97%
“…The effects of vitamin D on glucose homeostasis, exerted mainly by its active form 1,25-dihydroxycholecalciferol, include the increase of peripheral and hepatic glucose uptake, the improvement in synthesis and secretion of insulin, the protection of b-cells from cytokine induced apoptosis and attenuation of inflammation (47, 54-56). It has been confirmed that insulin resistance affects obesity-related pro-atherogenic changes in lipid profile (57,58). Insulin resistance impairs the function of insulindependent hormone-sensitive lipase and lipoprotein lipase, which are involved in lipid metabolism, whereas insulin cannot act effectively due to obesity and dyslipidaemia (59,60).…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with the established function of apoA-I in facilitating reverse cholesterol transport and its anti-inflammatory properties, which could potentially mitigate GDM risk through enhanced lipid metabolism as well as reduced inflammation [ 27 , 28 ]. Similarly, the inverse association between HDL cholesterol and the risk of GDM is indicative of the protective role of high-density lipoproteins in cardiovascular health, potentially exerting a similar influence on GDM by modulating lipid homeostasis and insulin sensitivity [ 29 , 30 ]. On the other hand, dysregulated triglyceride levels may increase vulnerability to GDM, as suggested by the positive connection found between triglycerides and GDM risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a significant correlation was observed between fasting blood glucose levels and ESA in the case group ( P = .001). Another study conducted by Zolghadri et al, [ 11 ] which examined the incidence of abnormal glucose tolerance in patients with spontaneous abortion, found that patients with a history of repeated abortion had a higher rate of impaired glucose tolerance than the normal group. In our study, the mean fasting blood glucose levels in the ESA population were significantly higher than those in the control population, supporting the findings of the studies mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%